Genomics Characterization of Colistin Resistant Escherichia coli from Chicken Meat-the First Report in the United Arab Emirates - Habib, Ihab; Mohamed, Mohamed-Yousif Ibrahim; Elbediwi, Mohammed; Ghazawi, Akela; Khan, Mushtaq; Abdalla, Afra; Lakshmi, Glindya Bhagya (Foodborne pathogens and disease, 2024)
Plasmid-mediated colistin resistance is an emerging One Health challenge at the human-food-environment interface. In this study, 12 colistin-resistant carrying gene were characterized using whole-genome sequencing. This is the first report from locally produced chicken meat in the United Arab Emirates. The characterized isolates harbored virulence-associated factors ranging from 4 to 17 genes per isolate. The multilocus sequence type 1011 was identified in 5 (41.6%) isolates. Six (50.0%) of the isolates harbored . All of the isolates contained Incl2 plasmids. This study highlights for the first time chicken meat as a potential reservoir of carrying in the UAE. This study has implications for food safety and underscores the need for comprehensive surveillance strategies to monitor the spread of colistin resistance. Results presented in this short communication address knowledge gaps on the epidemiology of plasmid-mediated colistin resistance in the Middle East food production chain.